The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1007/bf02805978
|View full text |Cite
|
Sign up to set email alerts
|

Chronic desipramine and fluoxetine differentially affect extracellular dopamine in the rat prefrontal cortex

Abstract: The effect of chronic administration of desipramine or fluoxetine (10 mg/kg IP once a day for 2 weeks) on extracellular noradrenaline, serotonin and dopamine in the rat prefrontal cortex was studied by transcerebral microdialysis. Chronic desipramine increased extracellular noradrenaline and dopamine by three-fold as compared to saline controls. Acute challenge with 10 mg/kg desipramine increased by more than three-fold extracellular noradrenaline and dopamine in saline controls, but failed further to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 20 publications
3
38
1
2
Order By: Relevance
“…These authors suggested that such an effect could be a consequence of a direct blockade of DA uptake in cortical noradrenergic terminals since DMI concentrations can still be high 24 hours after the last administration. Hence, the lack of effect on basal DA overflow in the present experiments following our schedule of antidepressant administration (considerable shorter than that used by Tanda et al 1996) might point out that at the time interval between the last dose of antidepressant and DA assessment (approximately 36 hours) under our experimental conditions there is no significant drug concentration present in frontal cortical tissue. Moreover, these drugs did not modify the overflow of cortical DA induced by restraint in animals unexposed to previous chronic stress.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…These authors suggested that such an effect could be a consequence of a direct blockade of DA uptake in cortical noradrenergic terminals since DMI concentrations can still be high 24 hours after the last administration. Hence, the lack of effect on basal DA overflow in the present experiments following our schedule of antidepressant administration (considerable shorter than that used by Tanda et al 1996) might point out that at the time interval between the last dose of antidepressant and DA assessment (approximately 36 hours) under our experimental conditions there is no significant drug concentration present in frontal cortical tissue. Moreover, these drugs did not modify the overflow of cortical DA induced by restraint in animals unexposed to previous chronic stress.…”
Section: Discussionmentioning
confidence: 55%
“…The present results also showed that none of the antidepressants used altered basal DA overflow from frontal cortex in controls. In contrast, Tanda et al (1996) showed a significant increase in basal extracellular DA from medial prefrontal cortex following a 14-day treatment with a daily 10 mg/kg DMI dose in unstressed rats. These authors suggested that such an effect could be a consequence of a direct blockade of DA uptake in cortical noradrenergic terminals since DMI concentrations can still be high 24 hours after the last administration.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, other studies using SSRIs (Hjorth and Auerbach 1994;Bosker et al 1995a,b;Invernizzi et al 1995Invernizzi et al , 1996 or clomipramine (Gur et al 1999) failed to show any change in 5-HT 1A autoreceptor subsensitivity by this method. An increase in basal 5-HT levels after chronic SSRI administration, taken to be due to pre-synaptic 5-HT 1A and 5-HT 1B receptor desensitization, has been observed in cortex (Bel and Artigas 1993), hippocampus (Auerbach and Hjorth 1995) diencephalon (Rutter et al 1994) and prefrontal cortex (Tanda et al 1996) and, after chronic administration of clomipramine, in frontal cortex but not hippocampus (Gur et al 1999). A number of other studies have failed, however, to show increases in basal 5-HT levels in terminal areas after chronic administration of 5-HT uptake blocking drugs (unless the measurements were performed less than 24 hr after the last administration of the drug, in which case the effect is very likely due to the persistence of residual drug) (e.g., Hjorth and Auerbach 1994;Bosker et al 1995a,b;Invernizzi et al 1995Invernizzi et al , 1996.…”
Section: Serotonergic Receptors Of the 5-ht 1a Subtype Have Been Suggmentioning
confidence: 99%
“…in the rat (Ring et al, 2004;Steinberg, personal communication). It can be speculated that this latter neurochemical effect may be responsible for the activity of SSR149415 in the DRL-72 s procedure, as the specific NE reuptake inhibitor desipramine, which also increases extracellular levels of NE in the PFC (Tanda et al, 1996;Mateo et al, 1998), is active in DRL schedules (O'Donnell and Seiden, 1983;Richards and Seiden, 1991;Dekeyne et al, 2002). This hypothesis needs to be reconciled with the report that SSR149415 blocked the stress-induced release of cortical NE (Griebel et al, 2002a, c).…”
Section: Discussionmentioning
confidence: 99%